MODELAMIENTO DE LA ESTRUCTURA DEL ALUMINIO LIQUIDO MEDIANTE EL METODO DE DINAMICA MOLECULAR - Rojas Tapia, Justo A. (2000)
We use the classical molecular dynamics method (MD) to obtain an atomistic description of the diffusion and the structure of liquid aluminum in a wide range of temperatures (900 K - 2600 K). These studies use two-body long range oscillatory potentials. The numeric resolution of the motion equations is carried out by means of the Verlet algorithm. The MD simulation has been performed on a system of 256 particles using that short range order remains up to high temperatures. The height and shape of peaks suffer significant changes with the temperature, which evidences the peculiarities of changes in the liquid structure. The correlation radius decreases from 0,9 nm to 0,4 nm in the range of temperatures studied. We found that the first coordination number changes approximately in the interval of 12 - 8..5. The results of the measurements of the selfdiffusion coefficient in aluminum, carried out by means of the mean-squared displacement of the ions, are in agreement with experimental data.